2021
DOI: 10.1096/fj.202002285rr
|View full text |Cite
|
Sign up to set email alerts
|

PARP‐1 involves in UVB‐induced inflammatory response in keratinocytes and skin injury via regulation of ROS‐dependent EGFR transactivation and p38 signaling

Abstract: UV irradiation can injure the epidermis, resulting in sunburn, inflammation, and cutaneous tissue disorders. Previous studies demonstrate that EGFR in keratinocytes can be activated by UVB and contributes to inflammation. Poly (ADP‐ribose) polymerase‐1 (PARP‐1) is a nuclear enzyme and plays an essential role in DNA repair under moderate stress. In this study, we set out to understand how PARP‐1 regulates UVB irradiation‐induced skin injury and interplays with EGFR to mediate the inflammation response. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…Cui et al found that the ratio of Bcl-2 and Bax decreased, while p-ERK1/2 was up-regulated by UVB [ 64 ]. Chiu et al demonstrated that the p38 signaling pathway was also involved in UVB-induced photoaging in keratinocytes [ 65 ]. Ko et al also found that Nrf2 was suppressed by UVB and alleviated by ergothioneine [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cui et al found that the ratio of Bcl-2 and Bax decreased, while p-ERK1/2 was up-regulated by UVB [ 64 ]. Chiu et al demonstrated that the p38 signaling pathway was also involved in UVB-induced photoaging in keratinocytes [ 65 ]. Ko et al also found that Nrf2 was suppressed by UVB and alleviated by ergothioneine [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…ROS can be generated by all known NLRP3 activators to activate inflammasome [ 18 , 19 ]. Upon oxidative stress-induced DNA damage, PARP-1 can be activated by ROS and reciprocally further increase ROS production [ 33 ]. As we observed the decreased inflammasome complex formation in Parp-1 −/− BMDM, we wondered whether PARP-1 also plays a role in NLRP3 activators-induced ROS production.…”
Section: Resultsmentioning
confidence: 99%
“…5 d). Intriguingly, our previous work also showed that PARP-1 can positively regulate UVB-induced ROS production in keratinocytes which is partially resulting from EGFR transactivation [ 33 ]. Another study mentioned that PARP-1 activation by oxidative stress contributes to the impairment of mitochondrial integrity by decreasing MKP-1 expression in an ATF4-dependent manner then activating p38 and JNK, leading to mitochondrial ROS production [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human immortalized HaCaT keratinocytes, oral SCC Cal-27 and SAS cells were cultured in high glucose Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% FBS and 1% penicillin-streptomycin-amphotericin B. NHEKs (normal human epidermal keratinocytes) were obtained from normal adult human foreskin and isolated as described previously (Chiu et al, 2021). The experiments were conducted according to the Declaration of Helsinki principles and approved by the Ethics Committee of Mackay Memorial Hospital (Institutional Review Board codes 19MMHIS173e).…”
Section: Cell Culturementioning
confidence: 99%
“…TLRs, the major pattern recognition receptors for host defense, are expressed in keratinocytes (Lebre et al, 2007). On the other hands, UVB and reactive oxygen species (ROS) can lead to DNA damageassociated EGFR transactivation and inflammation in keratinocyte (Chiu et al, 2021). Moreover, the role of Blimp-1 in cell migration of keratinocytes and SCC was addressed.…”
Section: Introductionmentioning
confidence: 99%